Creative success and network embeddedness: Explaining critical recognition of film directors in Hollywood, 1900-2010 - Mark Lutter (Max Planck Institute for the Study of Societies, 2014)
This article analyzes how social network structures affect career success in a projectbased labor market. The literature on team success has shown that teams perform well if they integrate both weak and strong ties simultaneously. Applying the literature to careers in the creative industries, the study suggests that creative artists are more likely to receive critical recognition if they build their careers in both familiar project networks and heterogeneous sets of creative conventions. It is argued that familiarity and diversity operate as complementary elements in the development of innovative ideas. While diversity is important to maximize the flow of new ideas, it needs to be embedded within trustworthy and familiar network structures in order to fully develop its creative potential. The suggested mechanism is tested by means of full career data of 55,097 film directors, covering 478,859 directing jobs in 330,142 film productions during the years 1900-2010. It is shown that familiarity and diversity explain a considerable part of a director's critical success. Results from interaction effects show that diversity has greater effects on critical success if it is socially embedded within familiar social structures. The article contributes to the emerging understanding of the role of group processes and network structures in explaining individual career success. – – Dieser Artikel untersucht, wie soziale Netzwerkstrukturen Karriereerfolg auf einem projektbasierten Arbeitsmarkt bestimmen. Auf der Grundlage von Forschung zu Teamerfolg argumentiert der Beitrag, dass Karriereerfolg in Kreativberufen wahrscheinlicher wird, wenn Karrieren sich sowohl in vertrauten als auch in diversen, mit heterogenen Konventionen ausgestatteten Projektnetzwerken bewegen. Vertrautheit und Diversität wirken als komplementäre Elemente in der Entwicklung innovativer Ideen. Zwar fördert das Element der Diversität den optimalen Austausch neuer Ideen, allerdings muss es, damit sich sein kreatives Potenzial vollständig entfalten kann, zugleich in vertrauensvollen Netzwerkstrukturen eingebettet sein. Anhand eines vollständigen Karrieredatensatzes, der Karriereprofile von 55.097 Filmregisseuren in 478.859 Engagements und 330.142 Filmproduktionen in den Jahren 1900 bis 2010 einbezieht, wird dieser Mechanismus getestet. Es zeigt sich, dass sowohl Vertrautheit als auch Diversität einen Großteil des Kritiker- und Karriereerfolgs der Regisseure erklären. Interaktionseffekte zeigen zudem, dass Diversität einen stärkeren Effekt auf künstlerischen Erfolg ausübt, wenn sie in vertrauten Strukturen eingebettet ist. Insgesamt erweitert die Studie unser Verständnis davon, wie Gruppen- und Netzwerkstrukturen individuellen Karriereerfolg beeinflussen.
Keywords: 300